Morphological and histological study of coronary sinus in human hearts from north-western region of Uttar Pradesh and its clinical implication - Agarwal, Jolly; Agarwal, Anurag; Kumar, Virendra; Devendra Nath Sinha; Sudhahar Tamizhan; Naithani, Manisha (Asian Journal of Medical Sciences, 2022)
Background: Coronary sinus (CS) is the largest diameter vessel in the coronary venous network, which serves as the primary collector of cardiac venous blood. Because the coronary venous system is not prone to the effects of atherosclerotic disease, it may also serve as a potential avenue for coronary artery bypass. Aims and Objectives: The aim of the study was to provide morphological and histological data of CS for making an interventional device. Materials and Methods: The present study cross-sectional study. Thirty hearts of different ages and of both sexes (22 males and 8 females) and duration of study is 2 years procured from cadavers available in the Department of Anatomy, SRMS IMS, Bareilly, U.P, India, were taken. Results: The mean length of the CS is 36.83±17.29 mm. The width of CS at the point of opening in to right atrium is 4.92±3.53 mm. The mean length of CS in males was 41.44±11.37 mm. While in females the mean length of CS was 39.29±11.17 mm. Histological study by Orcein stain show different amount of elastic fibers in proximal, middle, and distal part. Conclusion: Morphological and histological study of the CS suggests this structure to be an independent, cardiac chamber with a mural structure similar to atrial myocardium and it may be target for study and ablation, in the future therapy of atrial arrhythmias.